Mandibular Metastasis as a Rare Presentation of Follicular Variant Papillary Thyroid Carcinoma: A Case Series - Hamdani, William; Patabang, Erwin A.; Haryasena , Haryasena; Ferianto, Djonny; Pieter Jr., John; Salman Ardi Syamsu (Faculty of Medicine, Hasanuddin University., 2025)
Introduction: Papillary thyroid carcinoma (PTC) is the most common endocrine malignancy. The follicular variant of papillary thyroid carcinoma (FV-PTC) represents a distinct histologic subtype that tends to spread hematogenously to distant organs, including bone. Mandibular metastasis from FV-PTC is exceedingly rare and may pose a diagnostic challenge, particularly when it precedes recognition of the primary thyroid lesion. Presentation of case: We report two Asian female patients presenting with mandibular masses. The first patient had a history of total thyroidectomy for papillary thyroid carcinoma (follicular variant) ten years earlier. Imaging revealed an extensive osteolytic lesion of the right mandible. Histopathology of an incisional biopsy confirmed metastatic PTC, and the patient underwent right hemimandibulectomy with immediate reconstruction using a titanium plate. The second patient presented with a large, painful left mandibular mass without any history or clinical evidence of thyroid disease. Imaging showed a destructive lytic lesion of the left mandible, while neck ultrasonography revealed no thyroid enlargement. Biopsy suggested FV-PTC of thyroid origin. The patient underwent left hemimandibulectomy with titanium plate reconstruction. Final histopathology in both cases confirmed FV-PTC metastasis to the mandible. Conclusion: Mandibular metastasis from FV-PTC is a rare manifestation that may occur as late recurrence after thyroidectomy or as the first indication of an occult thyroid carcinoma. Comprehensive diagnostic workup and appropriate surgical reconstruction are crucial to achieve local disease control and preserve function. Clinicians should consider metastatic thyroid carcinoma in the differential diagnosis of lytic mandibular lesions, even in the absence of a palpable thyroid